Pre-operative cellular dissociation grading in biopsies is highly predictive of post-operative tumour stage and patient outcome in head and neck squamous cell carcinoma - Jesinghaus, Moritz; Steiger, Katja; Stoegbauer, Fabian; Haller, Bernhard; Kolk, Andreas; Strassen, Ulrich; Pickhard, Anja; Wirth, Markus; Silva, Miguel; Budczies, Jan; Von Rose, Aaron Becker; Konukiewitz, Bjoern; et al. (British Journal of Cancer, 2020)
Background: Pre-operative treatment planning in head and neck squamous cell carcinoma (HNSCC) is mainly dictated by clinical staging, which has major shortcomings. Histologic grading is irrelevant due to its lack of prognostic impact. Recently, a novel grading termed Cellular Dissociation Grade (CDG) based on Tumour Budding and Cell Nest Size was shown to be highly prognostic for resected HNSCC. We aimed to probe the predictive and prognostic impact of CDG in the pre-operative biopsies of HNSCC. Methods: We evaluated CDG in n = 160 pre-therapeutic biopsies from patients who received standardised treatment following German guidelines, and correlated the results with pre- and post-therapeutic staging data and clinical outcome. Results: Pre-operative CDG was highly predictive of post-operative tumour stage, including the prediction of occult lymph node metastasis. Uni- and multivariate analysis revealed CDG to be an independent prognosticator of overall, disease-specific and disease-free survival (p < 0.001). Hazard ratio for disease-specific survival was 6.1 (11.1) for nG2 (nG3) compared with nG1 tumours. Conclusions: CDG is a strong outcome predictor in the pre-treatment scenario of HNSCC and identifies patients with nodal-negative disease. CDG is a purely histology-based prognosticator in the pre-therapeutic setting that supplements clinical staging and may aide therapeutic stratification of HNSCC patients.
CRIS-Team Scopus Importer:2023-03-08